FIDES QUERENS HARMONIAM VITAE - THALIATH, MAR JONAS (Asian Horizons, 2007)
Theology as such was not so speculative as perhaps it was made out to be a little prior to our own times. By the time we were introduced to theology it had become somewhat more of a positive science. But there were certainly elements of biblical exegesis, historical relation of theological development and so on. So it was not so abstract a kind of theology that we learned. It was somewhat intimately linked to the Bible and the history of dogma and the history of the church. Even so I think we still missed something. Theology was defined and handed down to us, according to the definition given by St Anselm, the 11th century theologian and Archbishop of Canterbury. You must all be familiar with what he said about theology. Others have taken this dictum of his and applied it as a definition to theology but it was never his intention to define theology. Fides querens intellectum - this was the sub-title of one of his books about the existence of God. There, in the first part he delved deep into the nature of any disquisition about God. And there he has this famous dictum: Fides querens intellectum - Faith searching through the understanding of its content. Faith tries to understand what is conceived in it, but not quite explicitly. There are many merits in this for use as a definition of theology. First of all, this dictum puts faith and theology in their proper relation. Theology is not something like a rediscovery of faith. Theology is something which presumes faith. Fides is faith which is already there; that intellectual assent of the theologian is there. He is only groping using the gift of God to understand it: /I querens intellectum".